Advanced polymer composites and polymers in the civil infrastructure - Hollaway, L. (Leonard)
In recent years, the fabrication technologies for the production of advanced polymer composites have been revolutionised by sophisticated manufacturing techniques. These methods have enabled polymer composite materials to produce good quality laminates with minimal voids and accurate fibre alignment. This book familiarises and provides a background to the understanding and use of advanced polymer composites in the civil infrastructure; numerous examples have been provided to illustrate the use and versatility of the material. Furthermore, the book discusses the current fabrication techniques, design methods and formulae for the design of structural composite systems. In addition it discusses the fundamentals of geosynthetics used in geotechnical engineering. The book introduces the fibres and matrices that are used to manufacture composites, their mechanical and in-service properties and their long term loading characteristics; all these properties are specifically associated with the construction industry. The chapters then discuss the design aspects for 'all composite' units, as well as systems used for the renewal of civil infrastructure. Finally, the book demonstrated the unique possibilities of combining composites with conventional materials to form units in which the various materials making up the unit are loaded in the mode that specifically suits their mechanical characteristics.